Development of calamansi (Citrus microcarpa B.) flavored candy from blue ternatea (Clitoria ternatea L.) flowers. - Abelarde, Ruby Jane N. (2016.)
The local claim is that ternatea has health value because it is antioxidant. However, there seems to be a gap of knowledge among local consumers on why ternatea is known as an antioxidant. This study aimed to utilize the Blue ternatea flowers to produce candy and to know the effects of the addition of calamansi and temperature on the antioxidant activity of the Blue ternatea leaves. The Blue ternatea petals were subjected to spray drying to produce the Blue ternatea powder (BTP). The BTP had moisture content (MC) of 5.09%, total soluble solids (TSS) of 29.0% and titratable acidity (TA) 0.21%. The BTP was less hygroscopic with a moisture pick up of 0.27% every 20 minutes for 60 minutes. At pH 5.12, the anthocyanin content of BTP was 24.0 mg/L and a radical scavenging activity (RSA) of 55.1% IA to 56.9% IA (Darroca, 2016, unpublished). Three concentrations of ternatea-calamansi paste were prepared for the candy formulatios: BTCA (5g BTP: 10ml calamansi extract); BTCB (10g BTP: 10mL calamansi extract); and BTCC (15g BTP: 10mL calamansi extract). The formulations were subjected to sensory analyses. Kramer?s Rank Sum test revealed that the three formulations were not significantly different from each other in terms of preference. However, BTCB was considered as the most preferred ternatea candy (MPTC) and was rated as ?Like Moderately? in terms of general acceptability. Effects of adding calamansi and temperature were observed in the physico-chemical characteristic, anthocyanin content, and RSA of the MPTC. The physico-chemical content of the MPTC were: TSS=37.7%, TA=0.48% and aw=0.47. The MPTC was less hygroscopic than the BTP with 0.08% moisture pick up every 20 minutes for 100 minutes. At pH 3.07, MPTC had an anthocyanin content of 22.5 mg/L and the RSA of 0.30% IA to 6.28% IA. Factors in the processing of calamansi-flavored ternatea candy had changed the %TSS, %TA, anthocyanincontent and RSA of ternatea powder.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Calamansi; Citrus microcarpa B; Blue ternatea; Clitoria ternatea L; Candy